Removal of Fe (II) ions from drinking water using Electrocoagulation (EC) process: Parametric optimization and kinetic study. Issue 3 (June 2019) - Das, Daisy; Nandi, Barun Kumar
Abstract: Presence of Fe (II) ions in drinking water across different parts of India is a serious health concern in recent years. To reduce the Fe (II) ions in drinking water, researches are now being carried out using efficient and economical methods like adsorption, electrocoagulation etc. In the present work, experimental studies were carried out to optimize various operating parameters of electrocoagulation (EC) for efficient removal of iron (Fe (II) ions) from drinking water. Further, total dissolved solids, turbidity, conductivity, salinity, pH was accessed to verify the quality of treated water. From experimental results it was observed that, initial pH of 6.34, current density of 2 mA cm −2 with inter-electrode distance of 1 cm, electrocoagulation time of 45 min, initial salt (NaCl) concentration of 0.33 g L -1, stirring speed of 400 RPM are the optimum operating parameters to produce drinkable water (Fe (II) ions <0.30 mg L -1 ) from tap water having initial Fe (II) ions of 20 mg L -1 . Kinetic analysis of EC process infers that Fe (II) ion removal follows the first-order kinetic model with respect to different operating parameters. The rate constant ( k ) increased from 0.0352 min -1 to 0.1087 min -1 when the current density was increased from 1 mA cm -2 to 2.5 mA cm -2, due to availability of higher amounts of aluminium ion flocs during EC. Experimental studies confirm that suspended flocs generated during electrocoagulation can be separated by centrifugal methods as well as microfiltration membrane to replace laboratory scale filter paper-based methods.